2021
DOI: 10.3390/foods10040791
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fortification with Raspberry Juice on the Antioxidant and Potentially Anti-Inflammatory Activity of Wafers Subjected to In Vitro Digestion

Abstract: The aim of this study was to investigate the effect of raspberry juice addition on the content of phenolic compounds and the antioxidant activity of wafers. The research was carried out on non-supplemented wafers (control) and wafers in which water was replaced with raspberry juice in the amount of 10%, 20%, 50%, 75% and 100%. The potential bioavailability of the phenolic compounds after in vitro digestion was also determined. As shown by the consumer assessment, wafers in which the water was replaced with 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…To counteract oxidative stress, antioxidants are molecules in which single electrons or hydrogen atoms react to free radicals in oxidized cells and tissues (Maksimović et al, 2013;Tarasevičienė et al, 2020). As mentioned, raspberries are a rich source of natural antioxidants because it contains large amounts of phenols, flavonols, and anthocyanins and is, therefore, a free radical scavenger (Nardini & Garaguso, 2020;Szymanowska et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…To counteract oxidative stress, antioxidants are molecules in which single electrons or hydrogen atoms react to free radicals in oxidized cells and tissues (Maksimović et al, 2013;Tarasevičienė et al, 2020). As mentioned, raspberries are a rich source of natural antioxidants because it contains large amounts of phenols, flavonols, and anthocyanins and is, therefore, a free radical scavenger (Nardini & Garaguso, 2020;Szymanowska et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…(2021) reported that the substitution of WF with rye, oat, barley, or corn flour had a negative effect on the sensory properties of wafers in terms of sensorial colour, texture, and taste acceptability. In a recent study, the replacement of water in wafer formulations with raspberry juice did not significantly affect the sensory properties of the wafers except the sensorial colour (Szymanowska et al ., 2021). In conclusion, although GP addition did not significantly affect the sensory properties such as texture, colour, taste, odour, and overall acceptability, the increasing particle perception with higher concentrations is a disadvantage for the consumption.…”
Section: Resultsmentioning
confidence: 99%
“…However, metabolism studies have shown that ellagitannins with different polymerization degrees are hydrolyzed into single ellagic acid molecules and further metabolized in the small intestine and colonies [ 1 , 8 , 9 ]. From the nutritional perspective, ellagitannins have been found to exhibit strong antioxidant activities [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ], and anti-inflammatory effects [ 3 , 17 , 18 , 19 , 20 ], with great capability to weaken gastric ulcers, inhibit the growth of bacteria [ 21 , 22 ], fungi [ 23 ] and virus [ 24 , 25 ] and suppress the proliferation of cervical cancer cells [ 26 , 27 ]. In addition, ellagic acid has also received much attention for its antioxidant [ 28 ], anti-inflammation [ 29 ], and antiviral activities [ 30 ].…”
Section: Introductionmentioning
confidence: 99%